Insatiable appetite : the United States and the ecological degradation of the tropical world - Tucker, Richard P., 1938- (University of California Press, 2000)
This text presents a history of the transformation of the tropics in modern times, pointing ultimately to the declining biodiversity that has resulted from the domestication of widely varied natural systems.
Keywords: Tropical crops -- Economic aspects -- History -- 20th century.; Tropical crops -- Environmental aspects -- History -- 20th century.; Investments, American -- Tropics -- History -- 20th century.; Environmental degradation -- Tropics -- History -- 20th century.; Tropical Climate; Environment; Cultures tropicales -- Aspect économique -- Histoire -- 20e siècle.; Cultures tropicales -- Aspect de l'environnement -- Histoire -- 20e siècle.; Environnement -- Dégradation -- Régions tropicales -- Histoire -- 20e siècle.; NATURE -- Natural Resources.; BUSINESS & ECONOMICS -- Environmental Economics.; BUSINESS & ECONOMICS -- Green Business.; HISTORY -- United States -- General.; Environmental degradation; Investments, American; Tropical crops -- Economic aspects; Tropics; Ontbossing.; Ecologische aspecten.; Verenigde Staten.; Ontwikkelingslanden.; 1900-1999; Samfundsvidenskab -- Økonomi.; History